Relative effects of melatonin and hydrogen sulfide treatments in mitigating salt damage in wheat - Khan, Sheen; Alvi, Ameena Fatima; Fatma, Mehar; Al-Hashimi, Abdulrahman; Sofo, Adriano; Khan, Nafees A. (Frontiers in Plant Science, 2024)
Soil salinity poses a significant threat to agricultural productivity, impacting the growth and yield of wheat (Triticum aestivum L.) plants. This study investigates the potential of melatonin (MT; 100 µM) and hydrogen sulfide (H2S; 200 µM sodium hydrosulfide, NaHS) in the tolerance of wheat plants to 100 mM NaCl. Salinity stress induced the outburst of reactive oxygen species (ROS) resulting in damage to the chloroplast structure, growth, photosynthesis, and yield. Application of either MT or NaHS augmented the activity of antioxidant enzymes, superoxide dismutase, ascorbate peroxidase, glutathione reductase, and reduced glutathione (GSH) levels, upregulated the expression of Na + transport genes (SOS1, SOS2, SOS3, NHX1), resulting in mitigation of salinity stress. Thus, improved stomatal behavior, gas-exchange parameters, and maintenance of chloroplast structure resulted in enhanced activity of the Calvin cycle enzymes and overall enhancement of growth, photosynthetic, and yield performance of plants under salinity stress. The use of DL-propargylglycine (PAG, an inhibitor of hydrogen sulfide biosynthesis) and p-chlorophenyl alanine (p-CPA, an inhibitor of melatonin biosynthesis) to plants under salt stress showed the comparative necessity of MT and H2S in mitigation of salinity stress. In the presence of PAG, more pronounced detrimental effects were observed than in the presence of p-CPA, emphasizing that MT was involved in mitigating salinity through various potential pathways, one of which was through H2S.